2022
DOI: 10.1049/cth2.12249
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of nonlinear Markov jump systems by control parametrisation technique

Abstract: This paper considers an optimal control problem of nonlinear Markov jump systems with continuous state inequality constraints. Due to the presence of continuous-time Markov chain, no existing computation method is available to solve such an optimal control problem. In this paper, a derandomisation technique is introduced to transform the nonlinear Markov jump system into a deterministic system, which simultaneously gives rise to an equivalent deterministic dynamic optimisation problem. The control parametrisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It can be easily confirmed that a switched linear system with Poisson jumps is a Markov jump linear system, which is widely studied in the literature (see, e.g., [13,14,15,16]). Although we can find extensive amount of works for studying the Markov jump nonlinear systems [17,18,19,20], most of them implicitly assume the non-existence of the finite-time escape in each of the subsystems. Therefore, these results available in the literature for Markov jump nonlinear systems are not directly applicable to switched RDEs studied in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be easily confirmed that a switched linear system with Poisson jumps is a Markov jump linear system, which is widely studied in the literature (see, e.g., [13,14,15,16]). Although we can find extensive amount of works for studying the Markov jump nonlinear systems [17,18,19,20], most of them implicitly assume the non-existence of the finite-time escape in each of the subsystems. Therefore, these results available in the literature for Markov jump nonlinear systems are not directly applicable to switched RDEs studied in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Example 4.7. We first apply Algorithm 1 to the scalar RDE (18). The algorithm gives the graph of the escape time as a function of initial states as in Fig.…”
mentioning
confidence: 99%